Effectiveness of Online Education in Achieving Indonesia's National Education Targets in Elementary School - Lely Medyawati (Budapest International Research and Critics University, 2021)
Now, the world facing covid-19 pandemic, all affected world countries in all areas, including Indonesia. The massive transmission of covid-19 cause the Indonesian government, especially education and culture ministry, do an innovation learning a distance learning by using online learning. Online learning earning as solutions in education, have positive and negative impact. Some problems appear about government policy was because status developed countries that are having a growth of equal. An Impact felt by most students parents and teachers and the effectiveness education learning in achieving its objectives. School residents felt that online learning not oriented on how is a learning process, but only in the result who can’t be held accountable.